Psychometric evaluation of diagnostic test instruments on physics wave material - AM, Muh. Asriadi; Sanam, Anna Isabela (Jurnal Penelitian dan Evaluasi Pendidikan, 2025)
This study aims to evaluate the psychometric quality of diagnostic test instruments on wave material in physics learning, with a focus on their validity and reliability. The instrument was validated by seven experts using the content validation method, which resulted in an average validity score of 0.849, indicating that the instrument is very valid. Confirmatory factor analysis (CFA) was conducted to test the model fit and validity of the instrument structure. The KMO test results showed a figure of 0.946, indicating the suitability of the data for factor analysis, while the Bartlett Test of Sphericity results confirmed that the intercorrelation data was not an identity matrix. The tested model showed a good fit to the data, with a CFI value of 0.948, TLI of 0.935, and RMSEA of 0.072. The model parameter estimates showed a significant relationship between the latent variables and the observed items, with a strong influence from the "Wave" variable. Although the Chi-square test results indicated a statistically poor fit of the model, this result could be influenced by the large sample size. Limitations of this study include the limited sample size of seven validators, which may not cover all perspectives. This study suggests that further research involving a larger number of validators and more in-depth analysis should be conducted to strengthen the results obtained. The results of this study are expected to contribute to the development of more effective diagnostic test instruments for physics teaching at the secondary school level.